Do tradeoffs structure antibiotic inhibition, resistance, and resource use among soil-borne Streptomyces? - Schlatter, Daniel C. (BMC Evol Biol, 2015)
BACKGROUND: Tradeoffs among competing traits are believed to be crucial to the maintenance of diversity in complex communities. The production of antibiotics to inhibit competitors and resistance to antibiotic inhibition are two traits hypothesized to be critical to microbial fitness in natural habitats, yet data on costs or tradeoffs associated with these traits are limited. In this work we characterized tradeoffs between antibiotic inhibition or resistance capacities and growth efficiencies or niche widths for a broad collection of Streptomyces from soil. RESULTS: Streptomyces isolates tended to have either very little or very high inhibitory capacity. In contrast, Streptomyces isolates were most commonly resistant to antibiotic inhibition by an intermediate number of other isolates. Streptomyces with either very high antibiotic inhibitory or resistance capacities had less efficient growth and utilized a smaller number of resources for growth (smaller niche width) than those with low inhibition or resistance capacities, suggesting tradeoffs between antibiotic inhibitory or resistance and resource use phenotypes. CONCLUSIONS: This work suggests that life-history tradeoffs may be crucial to the maintenance of the vast diversity of antibiotic inhibitory and resistance phenotypes found among Streptomyces in natural communities. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-015-0470-6) contains supplementary material, which is available to authorized users.